Geodromicus nipponensis - Shavrin, A. V.; Makarov, K. V. (Zenodo, 2019)
Geodromicus nipponensis (Watanabe, 1990) Figs 3, 13; Map 6. Psephidonus nipponensis Watanabe, 1990: 275 (type locality: Japan, Honshu: Gunma Prefecture, near Nidoage, Asama Plateau). Other references see in Shavrin [2018]. MATERIAL. 1 ♂, 1 ♀: 1–1.5 km upper mouth of lower reaches of Severyanka River, 44°19´58´´N 146°1´15´´E, 16.06.2017, Yu.N. Sundukov leg. (CS); 7 specimens: 2–3 km of road Rudnoye-Filatovskiy, 16.06.2014, Yu.N. Sundukov leg. (CS, MSPU); 2 specimens: lower reaches of Filatova River, 25– 27.06.2013, Yu.N. Sundukov leg. (CS); 1 ♂, 4 ♀♀: valley of Tyatina River, 1–2 km up-stream of mouth, 07– 10.06.2016, Yu.N. Sundukov leg. (CS, MSPU); 1 specimen: Saratovskaya River near Tyatina River, 21– 24.08.2014, Yu.N. Sundukov leg. (CS); 10 specimens: environs of Saratovskiy kordon, 2– 4.07.2014, Yu.N. Sundukov leg. (CS, MSPU); 1 ♂, 3 ♀♀: lower reaches of Saratovskaya River, 44°15´46´´N 146°06´13´´E, 14– 15.07.2014, Yu.N.Sundukov, L.A. Sundukova leg. (CS, MSPU); 1 ♂, 1 ♂: lower reaches of Sernovodka River, 43°54´54´´N 145°38´11´´E, swamp, 10.08.2014. Yu.N. Sundukov, L.A. Sundukova leg. (CS). ADDITIONAL MATERIAL. RUSSIA: 1 ♂, 2 ♀♀: Sakhalin, Yuzhno-Sakhalinsk, botanical garden, 16.06.2018, Yu.N. Sundukov leg.(CS); 1 ♂: Shikotan Island, Tserkovnaya Bay, 12– 15.08.2016, Yu.N. Sundukov leg. (CS). DISTRIBUTION. Russia: Sakhalin, Kurile Islands (Urup, Kunashir: Map 6, Shikotan). — Japan (Honshu). BIONOMICS. Specimens were collected on gravel banks of relatively big rivers flowing from Dokuchayev mountain range (Fig. 13); not recorded from thermal zones. REMARKS. Habitus as in Fig. 3. In the list of the studied material of G. nipponensis from Kunashir Island provided by Shavrin [2018] the same four labels were erroneously repeat-ed (page 176), which in fact belong to G. iburinus (page 170). Here, we list material from Kunashir that was used, but not cited by Shavrin [2018]. The species is recorded from Shikotan Island for the first time. Published as part of Shavrin, A. V. & Makarov, K. V., 2019, Contribution ...